Conceptualising slum in an urban African context. (February 2017) - Smit, Suzanne; Musango, Josephine Kaviti; Kovacic, Zora; Brent, Alan C
Abstract: Increasing urbanisation and the proliferation of slums require a holistic understanding of the urban metabolism of cities. However, existing urban metabolic analyses exclude a detailed understanding of how urban slums function and contribute to biophysical, including energy, flows. This paper aims at filling this gap by critically investigating the notion of the urban slum in general, the extent to which it differs in the African context, specifically in South Africa, and broadening the understanding of urban slum based on the concept of urban metabolism, using the multi-scale integrated analysis of societal and ecosystem metabolism (MuSIASEM) approach, which was applied to the Enkanini informal settlement in Stellenbosch, South Africa. The analysis shows that South Africa has a more nuanced typology of the notion of urban slums categorised as: (i) townships; (ii) housing-turned-slum; (iii) squatter camps; (iv) site and service settlements; (v) transit camps; and (vi) hybrid multi-structured settlements. Beyond these definitions, the case study illustrates that urban slums, however defined, are complex systems with their own internal flows and processes that are connected in a myriad of ways to the larger urban system. The investigation into the use of Time, Money and Energy in the Enkanini case further revealed the productive (hypercyclic) and consumptive (dissipative) nature of the components of the urban informal settlement. This type of analysis reveals new insights into the linkages between urban informal settlements and the city. Highlights: We review and critique the global perspective and understanding of slums. We consider slums in relation to urbanisation trends in the African context. We present a typology of slums and propose a further dimension for analysis. We explore the notion of slums within urban policy and planning. We reveal how urban metabolic analysis changes our understanding of slums.